Evaluation of double‐tuned single‐sided planar microcoils for the analysis of small 13C enriched biological samples using 1H‐13C 2D heteronuclear correlation NMR spectroscopy. (28th October 2021) - Moxley‐Paquette, Vincent; Wu, Bing; Lane, Daniel; Bastawrous, Monica; Ning, Paris; Soong, Ronald; De Castro, Peter; Kovacevic, Ivan; Frei, Thomas; Stuessi, Juerg; Al Adwan‐Stojilkovic, Danijela; Graf, Stephan; et al.
Abstract: Microcoils provide a cost‐effective approach to improve detection limits for mass‐limited samples. Single‐sided planar microcoils are advantageous in comparison to volume coils, in that the sample can simply be placed on top. However, the considerable drawback is that the RF field that is produced by the coil decreases with distance from the coil surface, which potentially limits more complex multi‐pulse NMR pulse sequences. Unfortunately, 1 H NMR alone is not very informative for intact biological samples due to line broadening caused by magnetic susceptibility distortions, and 1 H‐ 13 C 2D NMR correlations are required to provide the additional spectral dispersion for metabolic assignments in vivo or in situ. To our knowledge, double‐tuned single‐sided microcoils have not been applied for the 2D 1 H‐ 13 C analysis of intact 13 C enriched biological samples. Questions include the following: Can 1 H‐ 13 C 2D NMR be performed on single‐sided planar microcoils? If so, do they still hold sensitivity advantages over conventional 5 mm NMR technology for mass limited samples? Here, 2D 1 H‐ 13 C HSQC, HMQC, and HETCOR variants were compared and then applied to 13 C enriched broccoli seeds and Daphnia magna (water fleas). Compared to 5 mm NMR probes, the microcoils showed a sixfold improvement in mass sensitivity (albeit only for a small localized region) and allowed for the identification of metabolites in a single intact D. magna for the first time. Single‐sided planar microcoils show practical benefit for 1 H‐ 13 C NMR of intact biological samples, if localized information within 0.7 mm of the 1 mm I.D. planar microcoil surface is of specific interest. Abstract : Single‐sided planar microcoils offer versatile sample placement but suffer from decreasing B1 field with distance, potentially limiting complex multi‐pulse NMR sequences. Here, 2D 1 H‐ 13 C HSQC, HMQC, and HETCOR variants were compared and then applied to 13 C enriched broccoli seeds and Daphnia magna . Compared to 5 mm NMR probes, the microcoil showed a sixfold improvement in mass sensitivity (albeit only for a small localized region) and allowed for the identification of metabolites in a single intact D. magna .